Dynamic scale theory for characterizing surface morphology of layer-by-layer films of poly(o-methoxyaniline) - de Souza, N. C.; Silva, JR; Pereira-da-Silva, M. A.; Raposo, M.; Faria, R. M.; Giacometti, J. A.; Oliveira, O. N. (Amer Scientific Publishers, 2004)
The dynamic scale theory and fractal concepts are employed in the characterization of surface morphological properties of layer-by-layer (LBL) films from poly(o-methoxyaniline) (POMA) alternated with poly(vinyl sulfonic acid) (PVS). The fractal dimensions are found to depend on the procedures to fabricate the POMA/PVS multilayers, particularly with regard to the drying procedures. LBL films obtained via drying in ambient air show a more homogeneous surface, compared to films dried under vacuum or a flow of nitrogen, due to a uniform rearrangement of polymer molecules during solvent evaporation.
Keywords: dynamic scale theory; layer-by-layer films; poly(o-methoxyaniline); fractal dimension; molecular control